2021
DOI: 10.1182/blood-2021-154226
|View full text |Cite
|
Sign up to set email alerts
|

Interim Efficacy Analysis of a Phase II Study Demonstrates Promising Activity of the Combination of Pembrolizumab (PEM) and Entinostat (ENT) in Relapsed and Refractory (R/R) Hodgkin Lymphoma (HL)

Abstract: Introduction Histone deacetylase (HDAC) inhibitors have single agent activity in various types of lymphoma. They restore antigen-specific immune recognition in B-cell lymphoma cells and modulate programmed cell death (PD)-1 expression on circulating T-lymphocytes. Pembrolizumab (PEM) is highly active in Hodgkin Lymphoma (HL) and demonstrates a 12-month PFS of 46% in patients with R/R HL. Preclinical studies have shown synergism of this combination in mouse models of various tumors. We present th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Potentially more promising are PD-1/PD-L1 ICB and histone deacetylase inhibitor (HDACi) combinations. The combination of pembrolizumab with entinostat was investigated in 22 R/R cHL patients by Sermer et al (2020Sermer et al ( , 2021 in a phase 2 trial with an ORR of 86% (Table 3) [72,73]. Similarly, a phase 2 trial with camrelizumab, another PD-1 inhibitor, combined with decitabine, demonstrated improved response rates (ORR 95%, CMR 79%) compared with camrelizumab monotherapy (ORR 89%, CMR 32%) (Table 3) [42,43].…”
Section: Pd-1/pd-l1 Icb Combined With Other Agentsmentioning
confidence: 99%
“…Potentially more promising are PD-1/PD-L1 ICB and histone deacetylase inhibitor (HDACi) combinations. The combination of pembrolizumab with entinostat was investigated in 22 R/R cHL patients by Sermer et al (2020Sermer et al ( , 2021 in a phase 2 trial with an ORR of 86% (Table 3) [72,73]. Similarly, a phase 2 trial with camrelizumab, another PD-1 inhibitor, combined with decitabine, demonstrated improved response rates (ORR 95%, CMR 79%) compared with camrelizumab monotherapy (ORR 89%, CMR 32%) (Table 3) [42,43].…”
Section: Pd-1/pd-l1 Icb Combined With Other Agentsmentioning
confidence: 99%